PENGARUH PEMBERIAN PUPUK KALIUM DAN CAMPURAN KOMPOS TANDAN KOSONG KELAPA SAWIT DENGAN ABU BOILER TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BAWANG MERAH (Allium asacalonicum L.) - DIAN FIKRI ALFIAN; NELVIA NELVIA; HUSNA YETTI (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2015)
The research aims to study the interaction of several doses of potassium fertilizer and compost mixture of oil palm empty fruit bunches with boiler ash on growth and yield of onion. The research has been carried out experimentally in the form of Randomized Completely Design Factorial 3 × 4. The first factor is the potassium fertilizer consist of three levels and the second factor is the compost mixture of oil palm empty fruit bunches with boiler ash consist of four levels. Observation made were plants height, number of tubers, diameter of tubers and fresh weight of tuber per clumps sample and yield of tubers per plot. Data analyzed by ANOVA and further tested using by Duncan`s New Multiple Range Test (DNMRT) at the level of 5%. The results showed the application of potassium fertilizer and compost mixture of oil palm empty fruit bunches with boiler ash significantly affect on the diameter of tuber per clump samples and yield of tubers per plot but not significant for other observations. Application of 60 kg K2O/ha with a mixture of compost oil palm empty fruit bunches and boiler ash 7,5 + 0,25 tons/ha a good dose of the growth and yield of onion.